Analisis Faktor yang Berhubungan dengan Kualitas Tidur pada Remaja di SMPN 254 Jakarta - Fajar Arya Nugraha; Aisyiah Aisyiah; Tommy J. F Wowor (Universitas Malahayati Lampung, 2023)
ABSTRACT Adolescent sleep patterns have undergone extraordinary changes, including shorter sleep times, delayed sleep times, and the quality of adolescent sleep continues to decline. Poor sleep quality can result in physiological and psychological balance disturbances. To determine the factors associated with sleep quality in adolescents at SMPN 254 Jakarta. The researcher used the Analytical Descriptive method using a Cross Sectionalresearch design approach, with a sample of 135 people from grade 8 at SMPN 254 Jakarta.The research instruments consisted of the Depressions Anxiety Stress Acales questionnaire (DASS 42), sleep environment, International Physical Activity Questionnaire (IPAQ), Smartphone Addiction Scale-Short Version (SAS- SV), and sleep quality. The five questionnaires have been tested for validity and reliability with Cronbach's alpha coefficient values above 0.6. The data were analyzed using descriptive statistics to determine the factors associated with sleep quality in adolescents. The research results show that there is a relationship between environmental factors and the use of gadgets on the quality of adolescent sleep (p0.05) and there is no relationship between stress and physical activity on the quality of adolescent sleep (p0.05). Environmental factors and the use of gadgets are stronglyrelated to the quality of sleep in adolescents. It is expected that respondents can understandthe factors that influence sleep quality and pay attention to and improve sleep quality so that respondents feel satisfied with their sleep Keywords: Physical activity, sleep quality, environment, use of gadgets, stress ABSTRAK Pola tidur remaja telah mengalami perubahan yang luar biasa antara lain waktu tidur yang lebih singkat, waktu tidur yang tertunda, dan kualitas tidur remaja yang terus menurun. Kualitas tidur yang buruk dapat berakibat kepada gangguan keseimbangan fisiologi dan psikiologi. Mengetahui faktor yang berhubungan dengan kualitas tidur pada remaja di SMPN 254 Jakarta. Peneliti menggunakan metode Deskriptif Analitik dengan menggunakan pendekatan desain penelitian Cross Sectional, dengan sampel sebanyak 135 orang dari kelas 8 di SMPN 254 Jakarta. Instrumen penelitian terdiri dari kuesioner Depressions Anxiety Stress Acales (DASS 42), lingkungan tidur, International Physical Activity Questionnaire (IPAQ), Smartphone Addiction Scale-Short Version (SAS-SV), dan kualitas tidur. kelima kuesioner tersebut telah diuji validitas dan reliabilitas dengan nilai koefisien Cronbach’s alpha diatas 0.6. Data dianalisis dengan descriptive statistic untuk mengetahui faktor yang berhubungan dengan kualitas tidur pada remaja. Hasil penelitian menunjukan bahwa adanya hubungan faktor lingkungan dan penggunaan Gadget terhadap kualitas tidur remaja (p0,05) dan tidak terdapat hubungan stress dan aktivitas fisik terhadap kualitas tidur remaja (p0,05). Faktor lingkungan dan penggunaan Gadget sangat berhubungan dengan kualitas tidur pada remaja. Diharapkan responden dapat memahami factor-faktor yang mempengaruhi kualitas tidur serta memperhatikan dan meningkatkan kualitas tidur sehingga responden merasakan kepuasan terhadap tidurnya. Kata Kunci : Aktivitas fisik, Kualitas Tidur, Lingkungan, Penggunaan Gadget, Stress